2013
DOI: 10.1007/s00296-013-2782-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct medical costs associated with rheumatoid arthritis in Turkey: analysis from National Claims Database

Abstract: This study aimed to estimate and identify determinants of direct medical costs associated with rheumatoid arthritis (RA) in Turkey using nationwide real-world data. Using the Turkish National Health Insurance Database (2009-2011), RA patients (ages 18-99) were identified using International Classification of Disease Tenth Revision Clinical Modification (ICD-10-CM) codes. Patients were required to have two RA diagnoses at least 60 days apart and were grouped as prevalent and incident cases. The date of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…27 It is unlikely that patients in this study shouldered any medication cost since patients who had a chronic condition certified by their physician can have their medications fully reimbursed by the Turkish government. 24 Furthermore, the list price for IFX per vial was ₮1,229.49 Turkish Lira and for CT-P13, was ₮1,205.87 Turkish Lira, which represents less than a 2% difference between the products. The lack of a substantial difference between the prices for IFX and CT-P13 in Turkey could be considered a strength of this study and provided an opportunity to gain insight into factors other than price that potentially contribute to observed differences in practice patterns.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…27 It is unlikely that patients in this study shouldered any medication cost since patients who had a chronic condition certified by their physician can have their medications fully reimbursed by the Turkish government. 24 Furthermore, the list price for IFX per vial was ₮1,229.49 Turkish Lira and for CT-P13, was ₮1,205.87 Turkish Lira, which represents less than a 2% difference between the products. The lack of a substantial difference between the prices for IFX and CT-P13 in Turkey could be considered a strength of this study and provided an opportunity to gain insight into factors other than price that potentially contribute to observed differences in practice patterns.…”
Section: Discussionmentioning
confidence: 96%
“…In Turkey, tendering for pharmaceuticals occurs in all public hospitals, 24 and this may, in part, explain the regional variation observed in prescribing and switching practices. Factors, such as disease severity or patient preference for one product over another, unmeasured in this study, may also have contributed to the results observed here.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, members of the Turkish Grand National Assembly and the Supreme Court as well as foreign insurance holders and some military personnel were excluded from the UHI Fund in the SSI. The data have been used in several outcomes research studies .…”
Section: Methodsmentioning
confidence: 99%
“…In the drug therapy of rheumatoid arthritis, basic anti-inflammatory drugs, genetically engineered biological drugs (limited, due to the high cost of course treatment), glucocorticosteroids, non-steroidal antiinflammatory drugs are used (Arts et al, 2016;Kolbin, Kurylev, Proskurin, & Balykina, 2016). The cost of medical care for patients who have several chronic diseases at the same time (comorbid conditions) significantly exceeds the cost of treating patients who do not have them (Baser, Burkan, Baser, Koselerli, Ertugay, & Altinbas, 2013;Kers, Urozhayeva, & Steffen, 2015).…”
Section: Introductionmentioning
confidence: 99%